2013
DOI: 10.5005/jp-journals-10015-1209
|View full text |Cite
|
Sign up to set email alerts
|

Study of Dental Treatment Received by Attenders in Government General Dental Center/Hospital Dugbe, Ibadan-Nigeria: A 5-Year Longitudinal Retrospective Study

Abstract: A study to determine the different types of received patients attending the Government Dental Center/Hospital, Dugbe Ibadan, Nigeria between December 1999 and December 2004 and to see how this treatment is distributed among different sexes and age groups. Government Dental Center Dugbe, Ibadan, was the Pioneer Dental Center in the South-Western Region of Nigeria and was established in the precolonial era. The treatment pattern noticed was an alarming rate of extractions which accounts for 76.65% of all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
2
1
1
Order By: Relevance
“…Contrary to previous studies that reported less extractions in regular attenders (8,17), we did not find any significant difference in the number of extractions needed between the different categories of attenders. This could however be due to the fact that only relatively few regular attenders were involved in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to previous studies that reported less extractions in regular attenders (8,17), we did not find any significant difference in the number of extractions needed between the different categories of attenders. This could however be due to the fact that only relatively few regular attenders were involved in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Published works have shown that the routine use of dental services is poor globally, although worse in developing nations, and that most patients present at the dental clinic majorly for treatment of symptoms (1,2,10,15). Majority of our respondents were making their first contact with a dental clinic at the time of the extraction, which corroborates the findings from previous studies that majority of dental service users are problem oriented (1,8,10). Adegbembo (2) in a study in Ibadan, southwestern Nigeria, reported that only 9% of household had utilized dental services the previous year.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations